The shocking truth about energy - Leedy, Loreen. (Holiday House, 2010)
Comical characters explain the basics, including the many forms energy can take. Readers can learn how energy changes from one form to another so that the Sun's energy can end up in a lunch box and eventually in people's muscles. Easy-to-follow diagrams show different ways energy can be harnessed. For a green look at the topic, the pros and cons of each form of energy are outlined, and tips on how to use energy sensibly are included. This high-voltage introduction to energy combines physical science and environmental science with fun.